Selections of Local Yard Long Bean in 14 varieties - Sitthivohane, Insavai; Chathaokalor, Daovang; Bounma; Bounvilaisone, Soulaseng; Salitxay, Timnoy (Souphanouvong University Journal Multidisciplinary Research and Development, 2017)
Variety selection is provided for local variety conservation and variety will be their own of farmers to support much more productivity in high quality and quantity. This study will find out the high yield of local yard long bean and satisfactory of consumers and its result will be extent to farmers to grow in the future. The experimental design has established in farm of Plant Science Department, Faculty of Agriculture and Forest Resource, Souphanouvong University. Duration of study started date 10/12/2016 to 30/4/2017. Applying by Completely Randomized Design experimental design consists of with 14 varieties. The growth and yield data was collected as: height of stem, length of leaves, width of leaves, flowering age 50%, harvesting age, duration of harvesting, amount of pod per plant, length of pod, circumference of pod, weight of pod in gram, yield kilogram per square meter and satisfactory of consumers was assessed as: length of pod, color of pod, palatable, beauty, height of stem and satisfactory. Data was analyzed in Sirichai Statistics 6.07 program and Microsoft Excel 2010. The results revealed that T1 showed the best data on highest yield; it was produced 1.57 kg/m2. While, T6 was produced 1.42 kg/m2. For T3, T2, T11, T5, T8, T13, T12, T7 was produced middle productivity in ordering 1.15 kg/m2, 1.12 kg/m2, 1.09 kg/m2, 1.08 kg/m2, 1.06 kg/m2, 0.96 kg/m2, 0.93 kg/m2, 0.88 kg/m2. Some of treatments indicated small yield as T14, T9, T10 represented 0.47 kg/m2, 0.35 kg/m2, 0.31 kg/m2 and T4 showed lowest response on productivity parameters 0.30 kg/m2. The assessment of satisfactory of consumers in overall, every treatments show good data on satisfactory. It showed that T8 has the peak of satisfactory; its level of average was 4.47 scores. While, Treatment 1 (T1) had score 4.39 and other treatment followed with T6 = 4.22, T11= 4.00, T13 = 4.00, T12 = 3.93, T7 = 3.75, T3 = 3.70, T5 = 3.33, T2 = 3.19, T4 = 2.30, T9 = 2.26 and the least of satisfactory Level was T10 that presented 2.05 score.